APLIKASI MESIN PEMERAS KELAPA TENAGA HIDROULIS UNTUK MENINGKATKAN PRODUKTIVITAS MINYAK KELAPA MURNI PADA KELOMPOK TANI DESA NGIS - KARANGASEM - Priambadi, I G. N.; Sugita, I K.G.; Sudarma, I M.; Dewi, A.A.I.K.; Suartika, I M.; Aryani, N. W. S. (Buletin Udayana Mengabdi, 2016)
Based on existing resources appear creativity for some people such as the manufacture of virgin coconut oil (virgin coconut oil) to raise additional income for the family. The existence of the activity of artisans in the use of coconut to increase the value for primarily in the manufacture of virgin coconut oil is still small. This is due to the manufacturing process requires a lot of time and patience, making it less attractive to the public. Proses pembuatan minyak kelapa yang merupakan kendala terbesar adalah pemerasan parutan kelapa. During this time the people who have the activity of oil makers are still using hand strength to squeeze the grated coconut. Observations have been done on the field this stage it is a constraint, so this activity is less attractive to the public. Existence of this business actually has the potential to be developed, especially lately a lot of information about the benefits of virgin coconut oil (virgin coconut oil). Based on clinical trials conducted on this commodity turns VCO beneficial for health.
Keywords: virgin coconut oil, extortion, physical health